(untitled) (Palíndromo, 2018)
From the closing of Queermuseum exhibition in 2017, neofundamentalist manipulative strategies are acknowledged because they desubjectivate the individual expression of queer artists. It is talked about freedom of speech and subject’s erasing attempts because this work aims to debate the “other” suppression in the dictatorship of the “self” from the impossibility of freedom when in times of coercion. As secondary goals, it is admitted: theoretically discuss freedom of speech; reveal inside language a place of fire through artistic speech; and analyze the work of Bia Leite, exhibited in the show. Methodologically, a bibliographic research was made so it was possible to correlate the study with Leite’s work. By its conclusion, when approaching differences cartography, this research faces artivism as a speech tool used by sociopolitical movements, reinsuring resistance’s importance.